1981
DOI: 10.1111/j.1460-2466.1981.tb00448.x
|View full text |Cite
|
Sign up to set email alerts
|

“Memorable” Messages

Abstract: Some interpersonal messages are reported to be remembered for a long time and to haoe a profound influence on a person's life.During the course of a single day, hundreds of verbal messages are directed to us in face-to-face encounters for evaluation and response; during one's lifetime the quantity of interpersonal messages processed must be staggering. Most of these messages have a relatively short life; they are processed, responded to, and forgotten. Yet, there seem to be a few verbal messages which may be r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
132
3
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(142 citation statements)
references
References 8 publications
5
132
3
1
Order By: Relevance
“…To be counted as a message, a unit of talk had to meet one of the following criteria derived from the memorable messages definition (Knapp, Stohl, & Reardon, 1981;Medved et al, 2006;Stohl, 1986): (a) the participant quoted the specific words a parent had said, which reflects that memorable messages are remembered for a long period of time; or (b) the participant explained a lesson learned from a parent, even if an associated, discrete message was not recalled, which reflects that memorable messages are perceived to have a lasting influence on the recipient's life. From the data, 346 messages from parents were identified.…”
Section: Methodsmentioning
confidence: 99%
“…To be counted as a message, a unit of talk had to meet one of the following criteria derived from the memorable messages definition (Knapp, Stohl, & Reardon, 1981;Medved et al, 2006;Stohl, 1986): (a) the participant quoted the specific words a parent had said, which reflects that memorable messages are remembered for a long period of time; or (b) the participant explained a lesson learned from a parent, even if an associated, discrete message was not recalled, which reflects that memorable messages are perceived to have a lasting influence on the recipient's life. From the data, 346 messages from parents were identified.…”
Section: Methodsmentioning
confidence: 99%
“…Questions on the interview guide asked participants to describe their vision of the "ideal" physician-patient relationship, how the experience and expression of emotion fit in their perspective on appropriate physician-patient interactions, and what significant events in their medical training contributed to the development of their perspectives on physician-patient relationships. Additionally, we adapted a version of the memorable message interview schedule originally created by Knapp, Stohl, and Reardon (1981) in order to tap into how informal conversations throughout the students' professional socialization have helped to construct their identities. Previous researchers have used adapted versions of memorable message questions to yield interesting findings about socialization processes (e.g., Stohl, 1986).…”
Section: Data Collection and Analysis Proceduresmentioning
confidence: 99%
“…R. Goldsmith and D. B. Pillemer of at most several days. In contrast, Knapp, Stohl and Reardon (1981) examined recall of statements spoken days, months or years earlier in the course of everyday activities. Since the conversations occurred in the uncontrolled contexts of the respondents' personal lives, the authors focused on subjective perceptions of verbatim memory rather than recognition accuracy.…”
mentioning
confidence: 99%
“…The memories also appeared stable over time; a test-retest study spanning 5 months showed a high degree of message consistency. Knapp et al (1981) discovered that the messages fulfilled a common function. The statements were concise, usually one sentence, and often prescriptive; 60 per cent contained rules for behaviour.…”
mentioning
confidence: 99%